AN INVENTORY OF INDIGENOUS PLANTS USED AS ANTHELMINTICS IN AMATHOLE DISTRICT MUNICIPALITY OF THE EASTERN CAPE PROVINCE, SOUTH AFRICA - Wintola, Olubunmi Abosede; Afolayan, Anthony J. (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Intestinal parasitic infections are among the most common chronic human infections in developing countries; particularly within thetropical and subtropical regions. An ethno-botanical survey was carried out to document medicinal plants used for the treatment of intestinal wormsin Amathole District Municipality of the Eastern Cape Province (ECP), South AfricaMaterials and methods: A questionnaire-guided interview of the indigenous people by random sampling was done with the help of an interpreterduring the survey of the district.Results: Medicinal plants mostly used for traditional management of intestinal worms were selected from 13 plant families: Alliaceae,Anacardiaceae, Asphodelaceae, Asteraceae, Crassulaceae, Dracaenaceae, Fabaceae, Hypoxidaceae, Lamiaceae, Longaniaceae, Punicaceae,Polygonaceae, and Verbenaceae. Out of these, Hypoxis hererocallidea (17%), Strychonos henningsii (14%), Rumex lanceolatus (12%), Ozoroamucronata (9%) and Acacia karoo (9%) belonging to the families Hypoxidaceae, Longaniaceae, Polygonaceae, Anacardiaceae and Fabaceaerespectively were found as the most cited, the least cited plant was Cotyledon orbiculata (2%). Leaves and roots from these plants were found to commonly used (36%), followed by the root (27%), bark (14%), the bulb and stem (9%), and rhizome collectively constitute (5%). Oral method administration by decoction (50%) and infusion (39%) was however found to be a common method by respondents.Conclusion: The current study however showed that ethno-pharmacological knowledge of the traditional healers in ECP largely depends on naturallygrowing species, documentation of which will go a long way in validating the therapeutic uses and safety of these plants as anthelmintic plants.